Effects of Satureja brevicalyx essential oil inhalation on coping premenstrual syndrome - Alvarado-García, Paul Alan Arkin (2022)
Introduction: The aim of this research was to evaluate the effects of Satureja brevicalyx essential oil inhalation on premenstrual syndrome. Methods: The oils were extracted by hydro-distillation using a modified Clevenger-type apparatus and chemical composition was performed by Gas chromatography-mass spectrometry (GC–MS). Furthermore, a quasi-experimental study was conducted, where 61 participants were divided in two groups, comprising an experimental with essential oils and a control group with no treatment. Main psychological symptoms were assessed with the used of Zung Self-Rating Anxiety Scale (SAS) and Zung Self-Rating Depression Scale (SDS) as well as total score of premenstrual syndrome was evaluated with Premenstrual Syndrome Scale (PMSS). Results: chemical analysis showed that linalool (17.6%) was the main component. All variables showed a decrease in posttest study phase in comparison with pretest in experimental group (p <0.05). A large size effect was observed for anxiety (d = 1.25; Δ = 1.35). Besides, moderate changes were found for depression (d = 0.79; Δ = 0.81) and premenstrual syndrome total score (d = 0.62; Δ = 0.56). Conclusion: The essential oil of Satureja brevicalyx exerts a potencial use, especially for the treatment of psychological symptoms of premenstrual syndrome.